Implementation of Clean and Healthy Lifestyle Behavior with Children's Nutritional Status the During Covid-19 Pandemic - Cut Yuniwati; Fithriany (Science Midwifery, 2022)
The implementation of Clean and Healthy Lifestyle in the midst of the COVID-19 pandemic has become a serious problem in society. The application of clean and healthy living behavior in everyday life in the household can reduce the risk of disease and nutritional status in children. Achievement of optimal nutritional status can be influenced by several factors, namely direct, indirect and root causes. Direct factors consist of food consumption and infection status. Indirect factors consist of availability, food consumption patterns, hygiene, sanitation, and environmental health. The purpose of this study was to determine the Clean and Healthy Lifestyle with Child Nutritional Status in the midst of the Covid-19 Pandemic. This study is a systematic review using online databases, namely Scholar, Sciencedirect, ProQuest, and EBSCO. The keywords used are clean and healthy living behavior, Child Nutrition Status, Covid-19 Pandemic.The selection process used the PRISMA protocol so that 15 articles were obtained that met the inclusion criteria. The findings of the review show that adopting a good, clean and healthy lifestyle affects children's nutritional status. The application of clean and healthy living habits in household arrangements is influenced by knowledge, culture, socioeconomics, beliefs, and the availability of facilities or technologies. During the Covid-19 pandemic, parents can play a role in reminding, educating, providing role models and support, advising, and emphasizing the importance of clean and healthy living.